“Want to Learn” and “Can Learn”: Influence of Academic Passion on College Students' Academic Engagement - Zhao, Hui; Liu, Xiaoxian; Qi, Chunhui (Frontiers in Psychology, 2021)
Although research exists on the relationship between passion and engagement among employees, the mechanisms of academic passion on academic engagement among students needs to be elucidated. Guided by the broaden-and-build and situated cognition theories, we explored the positive effect of academic passion on academic engagement, the mediating effect of academic self-efficacy, and the role of teacher developmental feedback as a moderator in the relationship between academic passion and academic engagement. Based on a sample of 1,029 college students from universities in the Henan Province of China, the results showed that academic passion was positively related to academic engagement, academic self-efficacy partially mediated the relationship between academic passion and academic engagement, and teacher developmental feedback effectively moderated the relationship between academic passion and academic engagement. These findings explained the mechanism underlying the relationship between academic passion and academic engagement. Moreover, the findings highlighted important factors that promote college students' academic engagement.